Deciphering serotonin's role in neurodevelopment - Sharon M. Kolk (Frontiers Research Topics, 2014)
One of the most challenging questions in neurobiology to tackle is how the serotonergic system steers neurodevelopment. With the increase in serotonergic anxiolytic and antidepressant drugs, serotonin was thought to signal adversity or to serve as an emotional signal. However, a vast amount of literature is accumulating showing that serotonin rather mediates neuroplasticity and plays a key role in early developmental processes. For instance, selective serotonin reuptake inhibitors (SSRIs), serving as antidepressants, increase neurogenesis and trigger autism-related brain and behavioural changes during embryonic and perinatal exposure. Moreover, serotonin transporter gene variation is associated with alterations in corticolimbic neuroplasticity, autism-related neuroanatomical changes, as well alterations in social behaviour. Hence, the view is emerging that early life changes in serotonin levels influence the developmental course of socio-emotional brain circuits that are relevant for autism and other neurodevelopmental disorders. It is particularly exciting that the effects of embryonic and perinatal SSRI exposure and serotonin transporter gene variation on neurodevelopment seem to overlap to a large extent, at the cellular as well as the behavioural level. Yet, the precise mechanisms by which serotonin mediates neurodevelopment in the normal and ´autistic´ brain is unclear. Whereas serotonin has a placental origin during early gestation, serotonergic neurons develop during midgestation under the control of a cascade of transcription factors determining the fate of mid-hindbrain neurons that together for the Raphe nuclei. These neurons are among the earliest neurons to be generated, and because serotonin is released before any conventional synapses are formed, serotonin is suspected to influence crucial neurodevelopmental processes such as proliferation,migration and network formation. During late gestation they target their final destinations in, for instance, the cortex, where they affect the secretion of reelin. Reelin is a secreted extracellular matrix glycoprotein that helps to regulate processes of neuronal migration and positioning in the developing cortex by controlling cell-cell interactions. During the late prenatal and early postnatal phase (in rodents) serotonin further shapes the outgrowth of projecting neurons, synaptic connectivity, and the morphology of white fiber tracts. This is under the influence of transient serotonin transporter expression in (thalamo)cortical projections, sensory and prefrontal cortices and the hippocampus, as well as the local expression patterns of 5-HT1A, 5-HT1B and 5-HT3A receptors that each exert their specific roles in neuronal migration, remodeling of axons, and controlling dendritic complexity. There is also evidence that serotonin influences neural activity in locus ceroeleus neurons. Hence, serotonin appears to influence the development of both short- and long-distance connections in the brain. This Research Topic is devoted to studies pinpointing the neurodevelopmental effects of serotonin in relation to prenatal SSRI exposure, serotonin transporter gene variation, and autism/neurodevelopmental disorders, using a wide-variety of cellular and molecular neurobiological techniques like, (epi)genetics, knockout, knockdown, neuroanatomy, physiology, MRI and behaviour in rodents and humans. We especially encouraged attempts to cross-link the neurodevelopmental processes across the fields of prenatal SSRI exposure, serotonin transporter gene variation, and autism/neurodevelopmental disorders, as well as new views on the positive or beneficial effects on serotonin-mediated neurodevelopmental changes.